Empirical evidence on the difference between the effective and the statutory tax rates for listed groups in Germany - Jan, Andreas Felix (2016)
The difference between the statutory and effective tax rate for listed groups is a complex variable influenced by a variety of factors. This paper aims to analyze whether this difference exists for listed groups in the German market and tests which factors have an impact on it. Thus the sample consists of 130 corporations listed in the three major German stock indices. The findings suggest that the companies that pay less than the statutory rate clearly outweigh the ones that pay more, and that the income earned from associated companies has a significant impact on this difference.